The developmental trajectory of hippocampus across the human lifespan based on multimodal neuroimaging - Xiu WANG; Ning YANG; Ye HE; Zhe ZHANG; Xing-ting ZHU; Hao-min DONG; Xiao-hui HOU; Hui-jie LI; Xi-nian ZUO (Chinese Journal of Contemporary Neurology and Neurosurgery, 2014)
Background During the last 2 decades, more and more functional MRI (fMRI) researches have increasingly focused on both structures and functions of the hippocampal region to discover the relationship between hippocampus and memory. In order to reveal the normative pattern of individual development or aging processes of the hippocampus or further memory-related disease prediction, an investigation on such a brain structure's trajectory across the human lifespan is necessary.  Methods Regional volume is the most commonly used variable for the structural change of normal brain. The regional homogeneity (ReHo) and amplitude of low-frequency fluctuation (ALFF) are the two test-retest reliable metrics for detection of functional changes. We here investigate ReHo, ALFF and fractional ALFF (fALFF) based upon both structural and resting state fMRI of 125 subjects from 7 to 85 years old.  Results As results, significant age-related decreases were detected for volumes of bilateral hippocampus (corrected Ps = 0.000). In contrast, ALFF (corrected P = 0.034, β = -0.314), fALFF (corrected P = 0.059, β = - 0.687) and ReHo (corrected P = 0.005, β = - 0.330) demonstrated a trend of negative linear correlation with age in the left hippocampus.  Conclusions Our findings partly reflect the structure-function relationship of the hippocampus during the human lifespan.   doi: 10.3969/j.issn.1672-6731.2014.04.006